Analisis Manajemen Rantai Pasok Sayuran di Pasar Rakyat Kota Ngabang, Kabupaten Landak - Astrada, Astrada; Ardilla, Amanda Sandy; Wibawa, Erlinda Gilberta; Natalia, Desika Mery (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Distribution of agricultural products, especially vegetables around Landak district, is usually carried out in several ways, namely directly from farmers, through agents, and through wholesalers so that they can be sent to people's markets so that they have an impact on increasing prices received by consumers. The research method used is descriptive qualitative. The research was carried out from April 2024 to June 2024 at the Ngabang people's market, Landak Regency. The data collection method was carried out on 20 vegetable traders, 3 vegetable agents, 2 wholesalers and 5 vegetable farmers. The research results show that the amount of vegetable supply at the Ngabang people's market fluctuates which has an impact on uncertain prices. The factor causing uncertain prices is because the supply chain from farmers to consumers is still long, so the way to overcome this is by cutting the supply chain according to needs.